1988
DOI: 10.1002/j.1460-2075.1988.tb03221.x
|View full text |Cite
|
Sign up to set email alerts
|

The human Lyt-3 molecule requires CD8 for cell surface expression.

Abstract: We have previously identified a monoclonal antibody, T8/2T8‐5H7, which clustered serologically with CD8 monoclonal antibodies, but lacked reactivity with L cell transfectants expressing the human CD8 molecule (Lyt‐2 homologue). Based on these observations, we postulated that T8/2T8‐5H7 might recognize the human Lyt‐3 gene product. To test this hypothesis, we have isolated a full‐length cDNA encoding the human Lyt‐3 molecule and have characterized its product in additional transfection experiments. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…Although the DP phenotype can be induced in both CD4 and CD8 single-positive T cells, DP T cells with CD8␣␣ subunit are likely to derive from CD4 + T cells, since CD8 + T cells have the ␣␤ subunit. [7][8][9] In fact, mature CD4 + T cells were shown to become DP by stimulation with IL-4 and to have CD4 + CD8␣␣dim phenotype, 10,11 identical to the phenotype of DP LGLL cells. In addition, in our as well as Tonutti's cases, a significant proportion of the residual T cells other than DP T cells showed CD4 + , CD8 − phenotype, which also showed CD11b + , 56 + , 57 + phenotype expressed on the DP cells.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Although the DP phenotype can be induced in both CD4 and CD8 single-positive T cells, DP T cells with CD8␣␣ subunit are likely to derive from CD4 + T cells, since CD8 + T cells have the ␣␤ subunit. [7][8][9] In fact, mature CD4 + T cells were shown to become DP by stimulation with IL-4 and to have CD4 + CD8␣␣dim phenotype, 10,11 identical to the phenotype of DP LGLL cells. In addition, in our as well as Tonutti's cases, a significant proportion of the residual T cells other than DP T cells showed CD4 + , CD8 − phenotype, which also showed CD11b + , 56 + , 57 + phenotype expressed on the DP cells.…”
Section: Tablementioning
confidence: 99%
“…[7][8][9] Thymic DP T cells and peripheral CD8 single-positive T cells Correspondence: M Mizuki, Department of Hematology and Oncology, Osaka University Medical School, 2-2 Yamadaoka, Suita, Osaka 565, Japan; Fax: 81 6 879 3879 Received 1 July 1997; accepted 2 January 1998 express CD8␣␤, while CD4 single-positive T cells become DP on activation with IL-4, and the DP T cells express CD8 of ␣␣ type. 10,11 Intestinal epithelial lymphocytes (IEL) are a distinct T cell subset, which preferentially express CD8␣␣ and contain a DP population.…”
Section: Introductionmentioning
confidence: 99%
“…CD8 is encoded by two distinct genes, termed CD8␣ (or Lyt 2) and CD8␤ (or Lyt 3) and expressed on the cell surface as a mixture of disulfide-linked CD8␣␣ homodimers and CD8␣␤ heterodimers (2)(3)(4)(5)(6)(7). CD8␣ is a 34 -37-kDa transmembrane glycoprotein whose extracellular segment contains a compact 122-amino acid (aa) N-terminal Ig-like domain and an extended 48-residue stalk region.…”
mentioning
confidence: 99%
“…A putative N-glycosylation site was found at position Asn-81 as described for the human molecule. 4 We examined the expression of the feline CD8b by Northern blot analysis using our FTb-6 clone as a probe. We detected the presence of an approximately 1 .…”
Section: Discussionmentioning
confidence: 99%
“…2 The glycoprotein is expressed on the surface of suppressor/cytotoxic T lymphocytes either as a homodimer or multimer of the a -chain (CD8aa) or as a heterodimer of the a -and b -chains (CD8ab). 3 A predicted molecular weight of the human CD8b molecule is approximately 34 000 with a polypeptide chain of 210 amino acids, 4 while the mouse (Lyt-3) and rat (OX-8) molecules are 28 000-30 000 and 37 000 MW, respectively. 5,6 Functional studies on the human CD8b molecule demonstrated that the molecule is necessary for maturation of CD8 + cells 7 and its external portion might play an important role in augmenting interleukin-2 (IL-2) production.…”
Section: Introductionmentioning
confidence: 99%